Crazy sexy juice : 100+ simple juice, smoothie & nut milk recipes to supercharge your health - Carr, Kris (Hay House, Inc., 2015)
"Kris Carr's Crazy Sexy Juice is a completely original, up-to-date, and colorful (of course!) guide to the wonderful world of fruit and vegetable elixirs. 100+ all-new recipes--developed especially for this book--contain superpowers ranging from immunity boosters, inflammation fighters, happiness helpers, longevity leaders, mood fixers, and booty enhancers. The all-green healthful tonics and fruity and refreshing potions are organized by function, including The Cleansers, The Healers, The Boosters, and The Beautifiers. Fiber-rich superfood smoothies are likewise categorized, as star pH Warriors, Body Boosters, Age Defiers, and Superheroes. A section on Nut Milks helps you get your protein power on. Not only are there enough recipes to keep your juicer and blender busy through every season, but Kris also addresses every concern you may have about juicing and blending. From selecting the right equipment for your needs and budget, to choosing and storing the most nutritious produce, she takes you through every aspect of the process--and helps make it a habit that sticks for life. Whether you're an old pro at making liquid magic or if you're just starting out, you will experience juicing and blending as a fun and delicious journey into the healing powers of fresh, raw fruits and vegetables, as well as nuts and seeds. Here's what else you can expect from this essential, concise (crazy, sexy) reference: Flavor combinations that tantalize your palate Tips for blending and juicing on the go Handy lists of helpful kitchen tools The 411 on alkalinity and why it's important A pick of the crop nutrient guide Handy substitutions for food sensitivities Hints on handling mental and emotional hurdles that come with change Plus an easy 3-day cleanse and so much more Drink your veggies. Change your life. Join Kris Carr on yet another adventure in health, happiness, and the delicious food that can make a powerful impact on your overall vitality. Cheers!"--